Bridging the Competency Gap in Maritime State Asset Management - Annisa Sholihahwati; Wilhelmus Harry Susilo; Chanra Purnama; Yoga Adiyasa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This qualitative study investigates the critical determinants of State Asset (BMN) management competency within Indonesia's Directorate General of Sea Transportation (Ditjen Hubla), a pivotal institution for national maritime development. Despite significant investments, recurrent findings from the Supreme Audit Board (BPK) indicate systemic failures in BMN administration. Through in-depth interviews with 12 key personnel and thematic analysis of BPK reports (2020-2023), this research identifies a profound competency schism. Findings reveal that maritime civil servants often possess adequate technical operational knowledge but lack the essential public financial administration capabilities, particularly deep digital proficiency in the SAKTI system and adaptive problem-solving skills for non-routine cases. A significant